Tingkat Literasi Halal Remaja dan Strategi Penguatannya: Studi di Pesantren di Indonesia - Widitya Qomaro, Galuh (LAKPESDAM MWCNU Palengaan, 2023)
This study specifically aims to examine the level of halal literacy among teenagers in the Indonesian Islamic boarding school environment and strategies to increase Islamic boarding school youth's understanding of the term halal economy, both in the form of product use and services. Three research questions will be answered in this study: What is the strategy to strengthen halal economic literacy among Islamic boarding school students in contemporary Indonesia? What are the challenges of strengthening halal economic literacy among young Islamic boarding school students in Indonesia? Methodologically, this study is field research conducted based on quantitative research. Two data are used, namely primary data in the form of observations and secondary data in the form of statistical figures. After analyzing field data, this study found that Islamic boarding schools, especially among children and teenagers, can increase halal literacy through existing structured learning implemented in the Islamic boarding school environment. The literacy level of Islamic boarding school teenagers regarding the halal economy can be seen in the participants' knowledge of the halal lifestyle, reaching an increase of 12.50% from a pretest score of 77.50 to 90.00. Studi ini bertujuan khusus mengkaji tingkat literasi halal di kalangan remaja di lingkungan pesantren Indonesia, strategi bagaimana meningkatkan pemahaman remaja pesantren terhadap istilah ekonomi halal, baik berupa pemanfaatan produk maupun layanan jasa. Terdapat dua (2) pertanyaan penelitian yang akan dijawab dalam kajian ini; bagaimana strategi memperkuat literasi ekonomi halal di kalangan santri di Indonesia kontemporer? Apa saja tantangan penguatan literasi ekonomi halal di kalangan remaja santri di Indonesia? Secara metodologi, kajian ini merupakan penelitian lapangan yang dilakukan berdasarkan jenis penelitian kuantitatif. Data yang digunakan ada dua, yakni data primer berupa observasi dan data sekunder berupa angka statistik. Setelah melakukan analisa data lapangan, studi ini mendapati temuan bahwasanya pesantren, terutama di kalangan anak-anak dan remaja, dapat meningkatkan literasi halal melalui pembelajaran terstruktur yang ada dan diterapkan di lingkungan pesantren. Tingkat literasi remaja pesantren terhadap ekonomi halal terlihat dalam pengetahuan peserta terhadap gaya hidup halal, mencapai peningkatan sebesar 12,50% dari skor pretest 77,50 menjadi 90,00.